ANALITICAL POTENTIAL OF CONCEPTS ‘POLITICAL SYSTEM’ AND ‘POLITICAL REGIME’ - Laurėnas, Vaidutis; Šerpetis, Kęstutis (Politologija, 2015)
The article is dedicated to the discussion about the notions of the ‘political system’ and ‘political regime’ in the fields of its meanings as autonomous analytical constructions. The main arguments are that the ‘political system’ describes a stable and normal political process and determinate interrelations between power structures and civil society institutions as a complex sociopolitical unity. On the other hand, concept of ‘political regime’ stresses dynamic aspects of the government activity as a realization of the basic political functions. Pointing to the fact that a political system explains events and relations in the modern democratic context and a regime – its peculiarities in the process of decision-making, the authors share attention to specific negative aspects of the separate interpretation and recognition of the various forms in the national politics spheres. All these conditions may sharp influence over the quality of the authority decisions, feedback among political institutions as a civic interests representatives etc. And otherwise, this implies that the political systems and political regimes realize an isomorphic similarity for taking evasive action between them.